Substrate specificity of human ABCC4 (MRP4)-mediated cotransport of bile acids and reduced glutathione - Rius, Maria; Keppler, Dietrich (American journal of physiology. Gastrointestinal and liver physiology, 2006)
The multidrug resistance protein ABCC4 (MRP4), a member of the ATP-binding cassette superfamily, mediates ATP-dependent unidirectional efflux of organic anions out of cells.
First published November 10, 2005
Gesehen am 18.02.2021